COVID-19 Pandemic and Psychiatric Symptoms: The Impact on Parkinson's Disease in the Elderly - Janiri, Delfina; Petracca, Martina; Moccia, Lorenzo; Tricoli, Luca; Piano, Carla; Bove, Francesco; Imbimbo, Isabella; Simonetti, Alessio; Di Nicola, Marco; Sani, Gabriele; Calabresi, Paolo; Bentivoglio, Anna Rita (Frontiers in Psychiatry, 2020)
Background: The coronavirus disease 2019 (COVID-19) pandemic represents a condition of increased vulnerability and frailty for elderly patients with Parkinson's disease (PD). Social isolation may worsen the burden of the disease and specifically exacerbate psychiatric symptoms, often comorbid with PD. This study aimed at identifying risk/protective factors associated with subjective worsening of psychiatric symptomatology during the COVID-19 outbreak in a sample of individuals with PD aged 65 years or older. Methods: Patients with PD routinely followed at the outpatient clinic of Gemelli University Hospital, Rome, were assessed for subjective worsening of psychiatric symptoms through a dedicated telephone survey, after Italy COVID-19 lockdown. Patients' medical records were reviewed to collect sociodemographic and clinical data, including lifetime psychiatric symptoms and pharmacological treatment. Results: Overall, 134 individuals were assessed and 101 (75.4%) reported lifetime psychiatric symptoms. Among those, 23 (22.8%) presented with subjective worsening of psychiatric symptomatology during the COVID-19 outbreak. In this group, the most frequent symptom was depression (82.6%), followed by insomnia (52.2%). Subjective worsening of neurological symptoms (Wald = 24.03, df = 1, p = 0.001) and lifetime irritability (Wald = 6.35, df = 1, p = 0.020), together with younger age (Wald = 5.06, df = 1, p = 0.038) and female sex (Wald = 9.07 df = 1, p = 0.007), resulted as specific risk factors for ingravescence of psychiatric presentation. Lifetime pre-existing delusions, having received antipsychotics, and not having received mood stabilizer were also associated with subjective worsening of psychiatric symptomatology due to the COVID-19 pandemic. Conclusions: Individuals with PD and lifetime history of psychiatric symptoms may be exposed to increased vulnerability to the stressful effect of COVID-19 outbreak. Interventions aimed at reducing irritability and mood instability might have an indirect effect on the health of patients with PD during the COVID-19 pandemic.